Evaluation of effectiveness of education on knowledge and attitude of petrochemical companies’ staffs in south Pars region regarding substance abuse - A Hajebi; P Faridnia; MS Zarif (طب کار)
Abstract Background: Decreasing demand for drugs through raising awareness of the population regarding the harms and dangers of drug abuse is deemed as one of the important methods of substance abuse prevention. The present study has been conducted in order to evaluate the effect of education on knowledge and attitude of petrochemical companies’ staff members in south Pars region regarding substance abuse in summer 2006. Materials and Methods: The study was designed as an experimental research with a sample size of 224 individuals. Sampling was performed in a multi-stage manner. The material of the study was a researcher-designed questionnaire, including 21 items. Face validity of the questionnaire was appropriate and its reliability was acceptable through test- retest (r= 0.8). Analysis of the data included descriptive statistics (frequency, percentage, mean, and standard deviation) and analytical statistics (t-test, one way and two way ANOVA). Results: The research revealed the fact that education has a significant effect on knowledge and attitude of the staff members regarding substance abuse. This effect is more obvious on the staff members with high school diploma. On the other hand, the results show that the effect of education on knowledge and attitude of the staff members regarding substance abuse is significantly different among staff members with day shift workers comparing with the offshore workers. Conclusion: Decreasing demand is one of the major strategies in substance abuse prevention. Thus raising awareness among different population subgroups regarding the harms and dangers of substance abuse and their awareness regarding the noxious effects of substance on their physical and mental health, occupational, social and familial function can be considered as an effective means in different levels of substance abuse prevention. If case individuals receive this information and trust it, the probability of substance abuse will decline.